Water chemistry data for the River Frome, Dorset, UK, from 1965-2009 - Bowes, M.; Casey, H.; Hilton, J.; House, A.; Leach, D. (NERC Environmental Information Data Centre, 2011)
Data from weekly water quality monitoring of the River Frome at East Stoke, Dorset (National Grid Reference SY 867868). The dataset consists of nitrate, soluble reactive phosphorus, dissolved silicon, pH, alkalinity, potassium, sodium, calcium and magnesium concentrations for the entire 44-year monitoring period, with total phosphorus, total dissolved phosphorus, electrical conductivity, water temperature, chloride, sulphate and ammonium concentration data for periods within the monitoring period. Daily average river flow on the day of sampling (extracted from the National River Flow Archive) is included.
Chemistry data generated by FBA, IFE and CEH staff over last 44 years, including Harry Casey, Alan House and Jim Smith. Final project manager was Mike Bowes (CEH). River flow data supplied by 'UK National River Flow Archive'. Analytical methods are in the supporting paper. Mainly weekly sampling but some sample dates missing particularly after 1997. Data validated and erroneous values removed. Some total phosphorus data has been removed between 2004 and 2006 due to analytical errors caused by change in methodology. Between 2004 and 2006 some duplicate samples were taken to obtain correct TP data.
Keywords: Frome; Dorset; Water quality